Analisis Tata Kelola Strategis dalam Mendukung Keberlanjutan Dana Pensiun Skala Kecil di Indonesia - Nur Rahmawati; Catur Iswahyudi; Saiful Huda; Eska Almuntaha (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
Indonesia’s pension fund industry has shown relatively stable asset growth in recent years; however, small-scale pension funds (Group IV) have experienced a decline in the number of entities and increasing sustainability pressures. This situation reflects an institutional capacity gap within the financial services industry, particularly regarding the ability of smaller institutions to meet governance, risk management, and regulatory compliance requirements. Previous studies have largely focused on investment performance and actuarial solvency, while research examining the sustainability of small pension funds from a strategic governance perspective remains limited. This study aims to examine the factors affecting the sustainability of Group IV pension funds and to identify strategic governance approaches suitable for small-scale pension fund institutions. The study employs a descriptive qualitative approach using Financial Services Authority reports, pension regulations, and relevant governance and risk management literature. The findings indicate that sustainability pressures are primarily associated with limited economies of scale, human resource constraints, regulatory compliance complexity, and insufficient information system support. Furthermore, a gap exists between the regulatory framework of the industry and the implementation capacity of small pension institutions. Therefore, a proportional, adaptive, and risk-based strategic governance approach is required to strengthen the sustainability of small pension funds in Indonesia.